A German e-learning-training in the context of early preventive intervention and child protection: preliminary findings of a pre-post evaluation. Issue 1 (December 2016) - Bressem, Kristina; Ziegenhain, Ute; Doelitzsch, Claudia; Hofer, Alexandra; Besier, Tanja; Fegert, Joerg; Kuenster, Anne
Abstract Background In recent years, a number of government-sponsored initiatives have been implemented in Germany that are focused on early preventive intervention in child protection. In response to the need for interdisciplinary training in this area, the internet-based e-learning program "Early Preventive Intervention and Child Protection" was developed for professionals in the child welfare and health care systems working with families with infants and toddlers. The program is currently undergoing evaluation for effectiveness and user satisfaction. Methods In a pre-post design, users are requested to complete questionnaires that assess three measures of expertise: theoretical knowledge of relevant fields, the ability to correctly identify subtle signals of infant communication, and the ability to assess maternal sensitivity. This article presents the contents of the program and the pre-training results (N = 1.294 participants). Descriptive analyses as well as Pearson correlations and Bonferroni corrections of error were conducted using the statistical program SPSS v. 21.0. Results The findings show that a wide range of professionals are making use of the program, and that their existing theoretical knowledge about early preventive intervention, as well as their ability to identify subtle signals of infant communication, is relatively good. However, their ability to assess maternal sensitivity, which is considered a crucial indicator for the risk of child abuse, was low. Conclusions The outcome of the pre-training results indicates that professionals working in the area of child protection need to develop more capability in recognizing maternal sensitivity, in order to ensure early detection of families who are at risk and thus in need of support. Finally, the number of years of professional experience did not correlate with the scores on any of the three measures, which emphasizes the importance of providing interdisciplinary training in this area for all those working in child and family services, regardless of background.